Aspek Mutu dan Tingkat Kesukaan Konsumen terhadap Surimi Ikan Belut - Mokhamad Nasir Salasa, Rini Rahayu Sihmawati (AGROKNOW, 2014)
Abstract. Indonesia fishery action in globalization era has potential development prospect. This can be seen from food industry of fishery result getting increase and has many kind of product. One of the fishery food product which is developed in Indonesia is surimi. Surimi is fish miofibril protein which has been stabilized and produced through process level continually which contains of squeeze meat, no bones and head., washing,. Decrease of water, cryoprotectant adding, so it has functional function mainly gel forming and water tied. The research goal is know the quality aspect and consumer like of fish surimi according to chemistry test and organpleptic test. This research uses experiment method and group random design in factorial term. Factor one( I) is the adding of tapioca flour( T) with the level of 1 %, 5%, 10%. Factor two ( II) is sugar adding ( G) with the level 1%, 2.5%,4%, 5.5% three times repetition. Chemistry parameter (proximat) with protein test. fat and ash level. While organoleptic parameter for taste test, texture, flavor,colour. The research result shows that each factor shows that there is significant influence to the protein , fat , ash level. There is a significant interaction influence of protein and ash level. While the fat has no significant influence and protein level tends to have linear decrease with more sugar and flour adding. For fat level tends to decrease linier with more tapioca flour but with more sugar , the fat also increases. While the ash tends ro increase liniarly with the adding of tapioca flour and sugar. The best composition in this research match with the chemistry test shows the treatment of T1G1 and T3G1. While the organoleptic test which has been done to the panelis , the best treatment is T3G4 if it is compared to the other treatments , like category 60% in taste , very like 40% in the texture, like 60% in the flavor and like 67% in colour.Kata kunci : perikanan, surimi, ikan belut, tepung tapioka, gula